Comparative Study Of Market Mechanism In The View Of Islamic Economics And Conventional Economics - Uzlan Uzlan; Rizky Abdul Haq; Rifqoh Maulidah Nurul (IJED: International Journal of Economy Development Research, 2022)
The market is a place for economic activity where economic activity takes place naturally so that the rules of the game also occur naturally. So according to Islamic economics the market mechanism can occur naturally from the supply and demand side as it should. Furthermore, in terms of market mechanisms, the perspective of Islamic economics in principle rejects the existence of a price intervention if price changes occur due to a fair market mechanism. However, the market here requires morality, including: fair competition, honesty, transparency and justice. If these values have been upheld, then there is no reason to refuse market prices. And if deviations occur, it is the duty of the state to regulate them for the benefit of the people.